Utilization of the COBIT 2019 framework to identify the level of governance in internet services - Sandhy Fernandez; Muhammad Imanullah; M. Yoka Fathoni; Pahrizal Pahrizal (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Information and communication technology services at the University of Muhammadiyah Bengkulu are IT services that support IT needs in all sectors. Of all the IT services that have been implemented at this institution, there is one very crucial service, namely the internet connection service, where this internet connection service is needed by all existing information technology access. In managing this internet connection, a standardized feasibility calculation has not been carried out which results in it not being in accordance with the institutional business needs. Information technology governance is a process that is able to manage investment decisions related to Information Technology within the company in order to achieve the company's current and future needs. To achieve standardized governance, this research uses the COBIT 2019 framework which is the latest version of the development results from COBIT 5. The purpose of this study is to identify the extent to which the value of existing processes for internet connection services is currently and the value of the process achievement that refers to the standard. COBIT 2019 by calculating the maturity level value which represents the level of performance on internet connection services. From the results of the 2019 COBIT Design, LTIK Muhammadiyah Bengkulu University, it is known that those who score above 80 or must reach Capability Level 4 are APO13, BAI10, DSS02, DSS03 and DSS04, for a value of 100 there is APO12.